Developing a Thai Theological and Biblical Understanding of the World: Rethinking Thai Cosmology in Light of Divine Council theology - Hilderbrand, Kelly Michael (Transformation, 2021)
This article is an attempt to compare and contrast biblical divine council cosmology (Heiser, 2008) with Thai Buddhist cosmology. The Ramakien and the Three Worlds According to King Ruang are the primary cultural narratives of the Thai people. These narratives give us insight into the worldview of the Thai. By comparing the Thai worldview with the biblical worldview, we can see where they intersect and where they are in conflict. The goal of this article is to spark a dialogue for producing a Thai theological and apologetic perspective that takes seriously Thai cultural worldview understandings in light of divine council cosmology and develops new tools for reaching Thai culture with the Gospel.